From Data to Knowledge using the GEOSS platform to support Sustainable Development Goals. Issue 1 (June 2020) - Giuliani, Gregory; Mazzetti, Paolo; Santoro, Mattia; Nativi, Stefano; Bemmelen, Joost van; Colangeli, Guido; Lehmann, Anthony
Abstract: [no-abstract]